Artistic synthesis of philosophy and history in Diana Ackerman's Novel "The Zookeeper's Wife" - Prykhodko, Vira; Soloshenko-Zadniprovska, Nataliia; Viediernikova, Tetiana; Chernenko, Olha; Shulga, Iryna (My University, 2022)
The article is devoted to the problem of Diana Ackerman’s the creativity. She created a touching and extremely objective book ‘The Zookeeper’s Wife’ showing the people suffering from the humiliation of their human dignity. Diana Ackerman, with endless love and anxiety for her characters, describes what people close to her saw and experienced during World War II. Her novel, imbued with the intense deployment of tragic actions and deeds, does not leave indifferent neither literary scholars, nor readers. The purpose of the article is to analyze the transformation of the characters in Diana Ackerman's novel ‘The Zookeeper’s Wife’ in the context of the development of the theme of survival in ‘labor camps’, Jewish ‘ghetto’ during the occupation period in European countries. The results of the study are understanding that the novel created is not characterized by the typical image of the main character, but the sketches do not ignore the individual features in the character of the husband, son, friends, her surrounding people, reveal the national features of life. The plausibility of events in occupied Poland of historical significance is being recreated. The study concluded that the novel is the work of lifeaffirming, performed by a civil and patriotic pathos.

Стаття присвячена проблемі творчості Діани Акерман, яка створила зворушливу і надзвичайно об’єктивну книгу «Дружина доглядача зоопарку», що зображує страждання людей від приниження їхньої людської гідності. Діана Акерман з нескінченною любов’ю і тривогою до своїх героїв описує те, що бачили та переживали близькі їй люди під час Другої світової війни. Її роман, пройнятий інтенсивним розгортанням трагічних вчинків, не залишає байдужим ні літературознавців, ні читачів. Мета статті – проаналізувати трансформацію героїв роману Діани Акерман «Дружина доглядача зоопарку» у контексті розробки теми виживання у «трудових таборах», єврейського «гетто» в період окупації в європейських країнах. Результати дослідження вказують, що створений роман не характеризується типовим образом головної героїні, адже ескізи не ігнорують індивідуальні риси характеру чоловіка, сина, друзів, оточуючих її людей, розкривають національні особливості життя. У романі відтворено правдоподібність подій в окупованій Польщі, що мають історичне значення. В ході дослідження було зроблено висновок, що роман-твір життєстверджуючий, виконаний с громадянським і патріотичним пафосом.
Художній синтез філософії та історії в романі Діани Акерман "Дружина доглядача зоопарку"
Keywords: Diana Ackerman; The Zookeeper's Wife; Jewish theme; children of "war"; Діана Акерман; "Дружина доглядача зоопарку"; єврейська тема; діти "війни"